La corte como mare errorum en La Cisma de Ingalaterra - Schlieper, Hendrik (Cálculo y error. Recontando a Calderón. XX Coloquio Anglogermano sobre Calderón)

Edge-coloring 4- and 5-regular projective planar graphs with no Petersen-minor - Kidner, Arnott Jeffery Joel; Steffen, Eckhard; Yu, Weiqiang (arXiv:2512.14285)

Self-guided tomography of time-frequency qudits - Serino, Laura Maria; Rambach, Markus; Brecht, Benjamin; Romero, Jacquiline; Silberhorn, Christine (Quantum Science and Technology)
Abstract High-dimensional time-frequency encodings have the potential to significantly advance quantum information science; however, practical applications require precise knowledge of the encoded quantum states, which becomes increasingly challenging for larger Hilbert spaces. Self-guided tomography (SGT) has emerged as a practical and scalable technique for this purpose in the spatial domain. Here, we apply SGT to estimate time-frequency states using a multi-output quantum pulse gate. We achieve fidelities of more than 99% for 3- and 5-dimensional states without the need for calibration or post-processing. We demonstrate the robustness of SGT against statistical and environmental noise, highlighting its efficacy in the photon-starved regime typical of quantum information applications.

Broadband Nyquist Pulse Generation on TFLN Platform for Integrated Quantum Source - Kress, Christian; Mihaylov, Martin Miroslavov; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (PIERS Proceedings)
The generation of optically broadband Nyquist pulse sequences using an integrated Mach-Zehnder modulator (MZM) in a thin-film lithium-niobate (TFLN) platform with repetition rates of 5 to 32 GHz and optical bandwidths of up to 160 GHz is demonstrated. Nyquist pulse sequences with high optical bandwidth can be used as synchronization and control signals in quantum sources based on photon pair generation.

Variational integrators for a new Lagrangian approach to control affine systems with a quadratic Lagrange term - Konopik, Michael; T. Sato Martín de Almagro, Rodrigo; Maslovskaya, Sofya; Ober-Blöbaum, Sina; Leyendecker, Sigrid (Journal of Nonlinear Science)

Sich in Worte kleiden. Über das Verhältnis von Texten und Textilien - Kraft, Kerstin (Erzählte Mode. Transdisziplinäre Perspektiven auf Text- und Bildgewebe)

Experimental Dataset: Force and Displacement Measurements of Four Rubber-Metal Bushing Types from a Passenger Car under Harmonic Displacement Excitation - Schütte, Jan
This dataset contains experimental measurements of the radial dynamic and quasi-static characteristics of four different types of Rubber-Metal Bushings (RMBs) used in the suspension system of a passenger car under harmonic displacement excitation. For each bushing type, 2–3 individual specimens were tested. Quasi-static measurements were performed at a constant excitation frequency of 0.05 Hz with varying displacement amplitudes. Dynamic measurements were conducted with displacement amplitudes ranging from 0.04 mm to 0.3 mm and excitation frequencies of 2, 5, 10, ..., up to 100 Hz. The data is structured by bushing type, measurement mode, amplitude, and frequency, and is provided in *.csv and *.hrm format. It is intended to support further research in modeling rubber-metal bushings and parameter identification techniques.
Keywords: bushing; experimental data; rubber-metal-bushing; Dataset suspension

The Amelia Project - Episode 87 - King Arthur (537 AD) - Ulsberg Brager, Oystein; Thorne, Philip; Freudinger, Markus
"He came concealed, but he hath now revealed his true identity! Kneel for the mighty King Arthur!" The Amelia Project is a production of Imploding Fictions. This episode featured Alan Burgon as The Interviewer, Hemi Yeroham as Kozlowski, Owen Lindsay as Big Jim, Patrick Lamb as Gavin, Anne Weiner as the barmaid, Anne Marie Sheridan, Beus Lunaire, Lara Bozkurt, Nicola Ségur and Torgny G. Aanderaa as villagers, Jordan Cobb as Jackie Williams and Erin King as Mia Fox. The episode was written by Oystein Ulsberg Brager with story and audio editing by Philip Thorne, translations into Old English by Dr. Markus Freudinger, sound design by Eli Hamada Mcilveen, music by Fredrik Baden, graphic design by Anders Pedersen, production assistance by Maty Parzival, and casting assistance by Julia C. Thorne. The episode was recorded at RedP studio in Vienna, with engineering by Arpad Hadnagy and Oliver Illes and assistance by Paul Kraner. Website: https://ameliapodcast.com/ Transcripts: https://ameliapodcast.com/season-5

Otus Supercomputer - Ehtesabi, Sadaf; Hossain, Manoar; Kenter, Tobias; Krawinkel, Andreas; Ostermann, Lukas; Plessl, Christian; Riebler, Heinrich; Rohde, Stefan; Schade, Robert; Schwarz, Michael; Simon, Jens; Winnwa, Nils; et al.
Otus is a high-performance computing cluster that was launched in 2025 and is operated by the Paderborn Center for Parallel Computing (PC2) at Paderborn University in Germany. The system is part of the National High Performance Computing (NHR) initiative. Otus complements the previous supercomputer Noctua 2, offering approximately twice the computing power while retaining the three node types that were characteristic of Noctua 2: 1) CPU compute nodes with different memory capacities, 2) high-end GPU nodes, and 3) HPC-grade FPGA nodes. On the Top500 list, which ranks the 500 most powerful supercomputers in the world, Otus is in position 164 with the CPU partition and in position 255 with the GPU partition (June 2025). On the Green500 list, ranking the 500 most energy-efficient supercomputers in the world, Otus is in position 5 with the GPU partition (June 2025). This article provides a comprehensive overview of the system in terms of its hardware, software, system integration, and its overall integration into the data center building to ensure energy-efficient operation. The article aims to provide unique insights for scientists using the system and for other centers operating HPC clusters. The article will be continuously updated to reflect the latest system setup and measurements.
Keywords: Otus; Supercomputer; FPGA; PC2; Paderborn Center for Parallel Computing; Noctua 2; HPC

Liebestragödie. Genealogien einer französischen Gattung des 17. Jahrhunderts - Schlieper, Hendrik

Vexierbilder als gegenhegemoniales Moment. Strategien postmigrantischen Erzählens bei Andrea Karimé - Kißling, Magdalena; Seidel, Nadine (Literatur der Postmigration: Grundzüge, Formen und Vertreter_innen)

Maghemite nanoparticles synthesis via spray flame synthesis and particle characterization by hole in a tube sampling and scanning mobility particle sizing (HIAT-SMPS) (Applications in Energy and Combustion Science)
In order to standardize spray flame synthesis (SFS) studies, intensive work has been done in recent years on the design of burner types. Thus, in 2019, the so-called SpraySyn1 burner was introduced (SS1), which was subsequently characterized in numerical and experimental studies. Based on this research, a modification of the nozzle design was proposed, which has now been considered in the successor model, SpraySyn2 (SS2). As little is known about the effect of the nozzle adaptation on the particle formation, we operated both burners under identical operating conditions to produce maghemite. The final powder comparison showed that SS2 yielded considerable higher specific surface areas (associated with smaller primary particle sizes), lower polydispersity, and higher phase purity. To obtain further information on the size distributions of aggregates and agglomerates generated by SS2, aerosol samples were extracted by hole in a tube (HIAT) sampling and characterized by scanning mobility particle sizing (SMPS). Samples were extracted along the centerline at different heights above the burner (HAB) above the visible flame tip (>7 cm), and quenching experiments were performed to extract the aerosol samples at different dilution rates. Thereby, it was demonstrated that performing detailed quenching experiments is crucial for obtaining representative HIAT-SMPS data. In particular, agglomerates/aggregate sizes were overestimated by up to ~70 % if samples were not sufficiently diluted. If sufficient dilution was applied, distribution widths and mean particle mobility diameters were determined with high accuracy (sample standard derivation <5 %). Our data suggested the evolution of primary particle sizes was mostly completed <7 cm HAB and it was shown aggregates/agglomerates present above the visible flame were compact in structure (non- fractal). The mean diameter of the particle ensemble grew along the centerline from 6.9 nm (7 cm) to 11.4 nm (15 cm), while distribution widths grew from 1.42 to 1.52.
Keywords: Flame Spray Pyrolysis; SpraySyn2; Spray flame synthesis; Maghemite nanoparticles; Gas to particle-conversion; Hole in a tube sampling

Der Imperativ der Biographisierung und die Ambivalenzen individueller Verantwortungszuschreibung - Dahmen, Stephan (Responsibilisierung)

“A Short Introduction to the Film Glove and Touch Studies.” - Kraft, Kerstin

Post-configuration Activation of Hardware Trojans in FPGAs - Ahmed, Qazi Arbab; Wiersema, Tobias; Platzner, Marco (Journal of Hardware and Systems Security)
Keywords: General Engineering; Energy Engineering and Power Technology

Professionalisierung für Sprachbildung aus Sicht von Sachunterrichtsstudierenden – Langzeitwirkungen eines Vertiefungsseminars in der ersten Phase der sachunterrichtsdidaktischen Lehrer* innenbildung. - Gövert, Andre; Niederhaus, Constanze; Blumberg, Eva (Mehrsprachigkeit in der Schule – Sprachbildung im und durch Sachunterricht)

DaZ-Kompetenzen angehender Lehrkräfte des Faches Sachunterricht sowie der aus dem Sachunterricht hervorgehenden Fächer - Vasylyeva, Tetyana; Ehmke, Timo; Gövert, Andre; Kassem, Amani; Niederhaus, Constanze (Mehrsprachigkeit in der Schule – Sprachbildung im und durch Sachunterricht)

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

ProDaZ Online-Tool Deutsch - Lammers, Ina; Büttner, Denise; Krechter, Romina

Pillar[5]arene-based dually crosslinked supramolecular gel as a sensor for the detection of adiponitrile - Rodin, Maksim; Helle, David; Kuckling, Dirk (Polymer Chemistry)
An SPR-based dually crosslinked gel sensor for adiponitrile bearing pillar[5]arene responsive sites with a low limit of detection was developed.
Keywords: Organic Chemistry; Polymers and Plastics; Biochemistry; Bioengineering